A collection of model parameters describing the gasification behavior of different fuels under entrained flow conditions. (15th July 2021) - Netter, Tobias; Fendt, Sebastian; Spliethoff, Hartmut
Highlights: The "Solid Fuel Entrained Flow Gasification Database" is presented. Parameters for the simulation of entrained flow gasification are provided. The gasification behaviors of different fuels are compared. Kinetics, thermal deactivation and surface area development are addressed. Abstract: Entrained flow gasifiers can be fed with a variety of fuels. However, each fuel has its own gasification behavior resulting in different operating conditions and ideal design configurations. The optimum can  be determined by e.g. modelling and simulating their gasification behaviors. Therefore, models and their parameters are necessary, which consider the processes involved. A collection of model parameters describing results of experimental investigations under entrained flow gasification is included in the presented "Solid Fuel Entrained Flow Gasification Database". The database contains information about devolatilization, surface area development, thermal deactivation and the reaction kinetics including product gas inhibition of five lignites, five bituminous coals, one anthracite, two pretreated biomasses and one blend. Their determination in a wire mesh reactor, a pressurized high temperature entrained flow reactor, a structural analyzer and thermogravimetric balances is exemplary presented by four investigated fuels. Further the content of the database is explained and visualized by comparing the results with ten other fuels. Overall, the presented database is unique in its kind as it summarizes these insights and supplements it with further information. There is no other fuel database available, which covers model parameters and refers to validation data of such a broad range of fuels considering entrained flow gasification.